Sediment concentration and size at Galing River, Kuantan, Pahang - Fatin Adnin, Mohamad Prim Nasir (2013)
A study on sediment was conducted at the Galing River. Three different days was consumed in order to take the samples which are 28/02/13, 13/03/13 and 27/03/13. This study was conducted to determine the sediment concentration, range of sediment grain sizes, sediment discharge and factors influencing sediment transportation. Three sampling stations were chosen, the first one at upstream Galing River (Station 1), mid-stream Galing River (Station 2) and downstream Galing River (Station 3). Parameter were quantified for this study, namely; river discharge values or flow rate (in m3/s), depth and wide of river (in meter). In this study, sediment grain size is acquired through sieve analysis. For sediment concentration (mg/L), it is measured by Total Suspended Solid (TSS). While, sediment discharge (tonnes/mday) is calculated by using Engelund Hansen's sediment transport function. It is preferred to use Engelund Hansen as all samples passed this function's requirement compare than other function. Engelund Hansen function required median size (D50) larger than 0.15mm. Overall, the fmdings of the study show that the sizes of sediment at Galing River based on Udden-Wentworth scale fall between phi 0.5 to 0 (0.71 to 1.0mm) which indicates coarse sand type. On the other hand, the average suspended sediment concentration recorded for each station shows varying values. The values were 0.010mg/L at Station 1, 0.022mg/L at Station 2 and 0.015mg/L at Station 3. For sediment discharge, the values were 0.012tonnes/m-day at Station 1, 0.046tonnes/m-day at Station 2 and 0.034tonnes/m-day at Station 3. Lastly, factors influencing sediment transportation at Galing River were identified where the factors are size of sediment, rainfall, vegetal covers, human's activities (effluent and garbage), river's hydraulic (flow rate), soil erosion and river's geometric (width and depth).